State Court Protection of Reproductive Rights: The Past, the Perils, and the Promise - Johnsen, Dawn (Columbia Journal of Gender and Law, 2015)
In the United States constitutional system, the protection of individual rights depends upon the federal and state judiciaries. The role of the federal courts in protecting reproductive rights provides a particularly well known, if controversial, example. Roe v. Wade is among the most widely recognized of all judicial decisions.’ The U.S. Senate, for example, routinely questions Supreme Court nominees about their views on Roe, as well as Roe’s principal precedent, Griswold v. Connecticut.2 Although the Supreme Court’s invalidation in Roe of Texas’s criminal abortion ban continues to be debated, Griswold’s invalidation of a Connecticut law that made it illegal for even married couples to use contraception stands as a pillar of modern constitutionalism.